Effects of Acute Aerobic Exercise on Cognitive Flexibility Required During Task-Switching Paradigm - Bae, Seongryu; Masaki, Hiroaki (Frontiers in Human Neuroscience, 2019)
The present study aimed to investigate the effects of acute aerobic exercise on underlying neuronal activities associated with task-switching processes including both mixing and switch costs. A total of 29 healthy young adults (21.4 ±1.2 years) participated in this study. The experiment consisted of an exercise and a rest condition. In the exercise condition, participants completed 30 minutes of walking and/or jogging on a motor driven treadmill sufficient to achieve an intensity of 70% of maximum heartrate (HRmax). In the rest condition, participants rested quietly for 30 minutes. Both conditions were conducted on different days, and the order was counterbalanced across participants. Participants performed the task-switching paradigm (switching between two different tasks), after both exercise and rest conditions respectively. The P3 amplitude was smaller in the non-switch trial than the single trial only in the rest condition, but not in the exercise condition. In other words, more attentional resources were allocated to the non-switch trial requiring greater amounts of working memory following the exercise condition. Mixing and switch effects on the P3 component were influenced by acute aerobic exercise. This result suggests that acute aerobic exercise may serve to facilitate the flexibility of task-set reconfiguration and maintaining the task set in working memory. Furthermore, during the switch trials, the P3 latency was shorter in the exercise condition than in the rest condition. This result is consistent with the findings of previous studies, indicating that cognitive processing speed is increased only during task conditions requiring greater amounts of executive control. Our study clearly indicates that acute aerobic exercise may facilitate cognitive flexibility as well as other executive functions (i.e., inhibitory control and working memory).